Luz e sombra: uma interpretação de suas significações imaginárias nas imagens do cinema expressionista alemão e do cinema noir americano - Lira, Bertrand de Souza (2008)
The present investigation proposes an approach of light and shadow and their imaginary significations in the images of both German expressionist movie and the American noir movie, whose aesthetic experience is expressed through a contrasting bright/dark photography, loaded with symbolism. The interpretation of the imaginary significations of this imagistic material is based on Gilbert Durand´s imaginary anthropological theories that deal with a myriad of symbols gathered according to their semantic isomorphism and linked to more general structures named as Daily and nightly Image Regime . There come to gravitate, around such regimes, symbols attached to division and purification, ascensional and spectacular, with imaginary significations homological to Light and Good, and symbols associated to night, fall and animalism, isomorphic of Shadow and Evil